International Students and Autonomy in Service-Learning English for Academic Purposes Courses - Estela Ene; Honnor Orlando (Michigan Journal of Community Service Learning)
Finding an answer to the effectiveness of autonomous learning in contrast to traditional forms of teacher-directed learning has significant pedagogical ramifications. Our study sheds light on the effects of increased autonomy in SL on the development of students and the role of the instructor. Furthermore, we focus on international student experiences in order to understand the ramifications for their development, in the context of increased internationalization. Our study compares autonomous (self-directed) and instructor- (other-directed) groups of students who engaged in SL as part of a university-level English language course. We collected data from 143 students’ pre- and post-service surveys over 8 semesters. Both other-directed and self-directed groups benefited from the SL experience, suggesting that students can develop holistically in a SL English for Academic Purposes (EAP) course. Other-directed students appeared to benefit more in terms of learning about specific social issues, service, and the target communities. Self-directedness was associated with perceived language gains more than other-directedness. Due to its potential to support the multi-dimensional development of international students, we recommend SL EAP and make pedagogical suggestions.